2017
DOI: 10.1097/mcg.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Upper Versus Lower Endoscopy in the Diagnosis of Graft-Versus-Host Disease

Abstract: Upper and lower endoscopy had a similar diagnostic yield in patients with known or suspected GVHD involving the gut, even for patients presenting only with diarrhea. Because of its ease and safety upper endoscopy is the preferred initial endoscopic approach in patients with suspected gut GVHD, however flexible sigmoidoscopy is a reasonable other option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In our clinical practice, we generally do not use purgatives in patients who have received HSCT and who are undergoing lower endoscopy; the volume of diarrhoea in this patient population usually allows for adequate inspection of the mucosa without the need for additional bowel cleansers. Importantly, newer data suggest that upper and lower endoscopy have similar diagnostic yields, even in patients who present with diarrhoea 76,77 . If EGD is performed in such patients, duodenal biopsies have a diagnostic yield higher than other sites of the upper gastrointestinal tract 78 .…”
Section: Diagnosismentioning
confidence: 99%
“…In our clinical practice, we generally do not use purgatives in patients who have received HSCT and who are undergoing lower endoscopy; the volume of diarrhoea in this patient population usually allows for adequate inspection of the mucosa without the need for additional bowel cleansers. Importantly, newer data suggest that upper and lower endoscopy have similar diagnostic yields, even in patients who present with diarrhoea 76,77 . If EGD is performed in such patients, duodenal biopsies have a diagnostic yield higher than other sites of the upper gastrointestinal tract 78 .…”
Section: Diagnosismentioning
confidence: 99%
“…The organ with the highest sensitivity for biopsy remains controversial, some recommend gastric biopsies and others recommend rectosigmoid biopsies (16)(17)(18). The Lerner classification is the most widely used histopathological scoring system for acute intestinal GVHD based on apoptotic bodies, crypt destruction, and mucosal denudation.…”
Section: Discussionmentioning
confidence: 99%
“…We report the largest cross-sectional study to date on the management and safety of endoscopic evaluation of aGVHD in patients who have undergone HSCT. A number of prior studies have found that symptoms such as diarrhea often occur in the presence of aGVHD in the lower GI tract, warranting evaluation with FS, while upper GI symptoms such as nausea and vomiting warrant evaluation with EGD[ 6 , 14 , 16 , 18 , 19 , 22 ]. On the contrary, we found that combined EGD and FS with biopsies resulted in at least an 80% diagnostic yield in patients with any presenting symptom.…”
Section: Discussionmentioning
confidence: 99%